Investigasi Faktor Penentu Return Saham Pada Perusahaan Sektor Keuangan - Sejati, Fajar Rina; Pertiwi, Dian; Masampe, Ranny (Balance: Media Informasi Akuntansi dan Keuangan, 2025)
This empirical test was conducted to examine the effect of liquidity, profitability, leverage and activity on stock returns in financial sector companies listed on the Indonesia Stock Exchange. The population of this study is all financial sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2020, with a total of 81 companies. Using purposive sampling, a sample of 21 companies was obtained. This research uses a literature study method published on the website www.idx.co.id. The data analysis method used is multiple linear regression. The results showed that liquidity and profitability had no effect on stock returns. Meanwhile, leverage and activity have a negative effect on stock returns. Then, liquidity, profitability, leverage, and activity simultaneously affect stock returns.